Placental chorioangioma separation in third trimester after fetoscopic laser therapy: Report of a rare case - Ying Wang; Yuan Wei (Clinical Case Reports, 2023)
Abstract A primigravida received fetoscopic laser photocoagulation treatment at 25+1 weeks gestation as a chorioangioma enlarged to 61 × 46 × 52 mm. However, a cesarean section was performed due to the chorioangioma separated from the placenta at 32+2 weeks gestation. As the chorioangioma's blood supply were blocked, it was possible to provide expectant treatment.